The Influence of Intensity and Work Dicipline on Employee Performance (A Studi At the Berlian Makmur Jaya Consumer Cooperative) - Hilmi Fauzan; Neng Rianti; Putri Apriliani; Sevia Fitriani; Desfinta Maharani (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the effect of incentives and work discipline on performance in the Berlian Makmur Jaya Consumer Cooperative. The population in the study were all employees at the Koperasi Konsumen Berlian Makmur Jaya Cianjur. The samples taken were 42 people. Data collection techniques are interviews, documentation studies and Questionnaires. The data used the Classical Assumption Test method, Multiple Linear Regression, t test (partial test), f test (simultaneous test), and the coefficient of determination with the help of IBM Statisctic SPSS 22 software. Based on the research results, the value of Ftable was obtained with a significance level of 5% or 0 .05 obtained Ftable of 3.232. Fcount is 38.691 with a significance of 0.000 below 0.05, this shows Fcount (38.691) > Ftable (3.232), then if Fcount > Ftable, then H0 is rejected and Ha is accepted. This means that the incentive and work discipline variables simultaneously influence the employee performance variables at the Koperasi Konsumen Berlian Makmur Jaya Cianjur. Meanwhile, the value of the coefficient of determination is 0.665, this means that employee performance can be explained by incentives and work discipline variables of 66.5% while the remaining 33.5% is explained by other variables not examined in this study. The biggest influence on employee performance is the incentive variable. This is because the regression coefficient, incentives (1.171) is greater than work discipline (0.089).